2004
DOI: 10.1210/me.2003-0165
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic Acid Response Element-Dependent Regulation of Transcription by Orphan Nuclear Receptor Estrogen Receptor-Related Receptor γ

Abstract: The estrogen receptor-related receptor gamma (ERR gamma/ERR3/NR3B3) is the newest member of the ERR subfamily that also includes ERR alpha and ERR beta. All three isoforms share a high degree of amino acid identity especially in the DNA binding domain. ERR gamma is a constitutively active transcriptional activator that regulates reporter elements driven by steroidogenic factor 1 response element (SF-1RE) and estrogen response element. However, it has the highest potency on a derivative of SF-1RE present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 58 publications
(111 reference statements)
2
25
0
Order By: Relevance
“…Recent findings of several laboratories demonstrate that the sequence of DNA binding element is important in regulating the ERRγ transactivation function (Razzaque et al, 2004;Sanyal et al, 2004). Consistent with these reports, we found that the AAB of the ERRα gene and the synthetic 3x ERE which contain multiple ERE half sites, are very sensitive to ERRγ stimulation whereas 1x ERE and the NRRE of the MCAD gene are less responsive (Fig 6A).…”
Section: Differential Molecular Characteristics Of the Errα And Errγsupporting
confidence: 91%
See 1 more Smart Citation
“…Recent findings of several laboratories demonstrate that the sequence of DNA binding element is important in regulating the ERRγ transactivation function (Razzaque et al, 2004;Sanyal et al, 2004). Consistent with these reports, we found that the AAB of the ERRα gene and the synthetic 3x ERE which contain multiple ERE half sites, are very sensitive to ERRγ stimulation whereas 1x ERE and the NRRE of the MCAD gene are less responsive (Fig 6A).…”
Section: Differential Molecular Characteristics Of the Errα And Errγsupporting
confidence: 91%
“…It is known that ERRγ is a strong activator of selective response elements (Razzaque et al, 2004;Sanyal et al, 2004), interacts with PGC-1α Huss et al, 2002) and stimulates the ERRα gene promoter via the MHRE (Liu et al, 2005). Furthermore, treatment of HEC-1B cells with ERRγ siRNA significantly reduced the ERRα mRNA expression (Liu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Whether PGC-1 enhances or stabilizes binding of the ERR to MHRE is not clear; it is known that the receptor conformation can be modified and its activity modulated upon binding to the response element and by interaction with the coactivators (Klinge et al 2001, Loven et al 2001, Wood et al 2001, Hall et al 2002, Sanyal et al 2002. ERR exhibits different coactivator recruitments and transcriptional activity, depending on the response element (Sanyal et al 2004). Binding of ERR to the MHRE could change its conformation and increase interaction with PGC-1 , thus forming a strong activation complex.…”
Section: Discussionmentioning
confidence: 99%
“…Total DNA amounts in all cases were kept to a constant by using empty pcDNA3 vectors. Luciferase assays were performed as described elsewhere (37).…”
Section: Methodsmentioning
confidence: 99%